JUMPA Vol.3 No.1 Feb 2016 FAKTOR PENENTU KEPUASAN NASABAH PADA PT.BANK BUKOPIN: FAKTOR PENENTU KEPUASAN NASABAH PADA PT.BANK BUKOPIN - Riska Intania Hastari Perbanas Institute; Yohanes Ferry Cahaya Perbanas Insitute (Jurnal Manajemen dan Perbankan (JUMPA), 2016)
This study aimed to analyze the influence of Product Quality and Service Quality on Customer Satisfaction at PT. Bank Bukopin, either partially or simultaneously. The study design descriptive, whereas quantitative research. Population is the overall customer at. Bank Bukopin, Tbk Branch Gunung Sahari Jakarta, while the sample of 57 respondents, conducted by accidental sampling technique (convenience sampling). The analysis is correlation, regression and hypothesis testing. The results showed that: (1) There is a positive relationship is very strong between Quality Products to Customer Satisfaction (2) There is a positive relationship is very strong between the Quality of Service with Customer Satisfaction (3) the results of simultaneous testing shows that the Product Quality and Service Quality positive effect strong against Customer Satisfaction. and fit for use regression models to predict all of the independent variables on the dependent variable.